Dopamine D2 Receptor Is Involved in Alleviation of Type II Collagen-Induced Arthritis in Mice. (29th November 2015) - Lu, Jian-Hua; Liu, Yi-Qian; Deng, Qiao-Wen; Peng, Yu-Ping; Qiu, Yi-Hua
Abstract : Human and murine lymphocytes express dopamine (DA) D2-like receptors including DRD2, DRD3, and DRD4. However, their roles in rheumatoid arthritis (RA) are less clear. Here we showed that lymphocyte DRD2 activation alleviates both imbalance of T-helper (Th)17/T-regulatory (Treg) cells and inflamed symptoms in a mouse arthritis model of RA. Collagen-induced arthritis (CIA) was prepared by intradermal injection of chicken collagen type II (CII) in tail base of DBA/1 mice or Drd2 −/− C57BL/6 mice. D2-like receptor agonist quinpirole downregulated expression of proinflammatory Th17-related cytokines interleukin- (IL-) 17 and IL-22 but further upregulated expression of anti-inflammatory Treg-related cytokines transforming growth factor- (TGF-) β and IL-10 in lymphocytes in vitro and in ankle joints in vivo in CIA mice. Quinpirole intraperitoneal administration reduced both clinical arthritis score and serum anti-CII IgG level in CIA mice. However, Drd2 −/− CIA mice manifested more severe limb inflammation and higher serum anti-CII IgG level and further upregulated IL-17 and IL-22 expression and downregulated TGF- β and IL-10 expression than wild-type CIA mice. In contrast, Drd1 −/− CIA mice did not alter limb inflammation or anti-CII IgG level compared with wild-type CIA mice. These results suggest that DRD2 activation is involved in alleviation of CIA symptoms by amelioration of Th17/Treg imbalance.